Donner à voir le passage de la montagne de Gaule par les mots ou par l’image : héritages et acquis des géographes, voyageurs et cartographes sur l’itinéraire du col du Montgenèvre - Delphine Acolat (Belgeo)
Most authors, travelers or not, often conform to tradition and show cognitive schemas and sometimes outdated or stereotyped. We must distinguish those who attempted to reflect a seen and updated reality, in particular Ammianus Marcellinus about Montgenèvre pass in hivernal conditions. Mapping, such as we can know the substance or traces, thanks to maps of the Middle Ages, reveals a legacy and a dependence with the earlier texts. Mapping is physically limited in its details, and even if we don’t speak about informative drought, choices are indicative of the importance of strategic or political role of the relief, the sustainability of a system of thought and culture, and the likely mapping the writings of canonical authors.